Investigation of Viscosity Effects on Flow Rate and Pressure Drop in a PVC Fluid Transfer System Using Different Water Sources - Abutu, Joseph; Lekan Oladosu , Temidayo; James Abakpa Emmanuel; Atinuke Oluleye , Modupe; Emeka Daniel Oruonye; Ike Ogwuche , Christian (Journal of Advanced Industrial Technology and Application, 2026)
Fluid transfer systems are essential in domestic and industrial settings, requiring efficient design for fluid conveyance. This study developed a fluid transfer system with centrifugal pumps, gate valves, and PVC plumbing, ensuring structural stability with a metal frame weighing 28.9 kg and tank guides weighing 67.7 N and 47.6 N. Flow analysis showed turbulent conditions with a Reynolds number of 9160. Pressure drops were highest in the longest pipeline (0.171 N/m³) and significant at 90° elbows (0.1174 N/m³), compared to gate valves (0.0214 N/m³). Tests with rainwater, tap water, and stream water indicated rainwater had the highest flow volume (48.65 L in 20 min) and flow rate (2.43 L/min), while tap and stream water had lower rates (2.07 and 1.83 L/min). The experimental results confirms established fluid dynamics principles that higher viscosity fluids flow more slowly through pipes, substantiating the dependence of flow rate on fluid viscosity.